2011
DOI: 10.1016/j.epsl.2010.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of localized and diffuse deformation in the Tibetan Plateau from joint inversions of geologic and geodetic observations

Abstract: The spatial complexity of continental deformation in the greater Tibetan Plateau region can be defined as the extent to which relative motion of the Indian and Asian plates is partitioned between localized slip on major faults and distributed deformation processes. Potency rates provide a quantitative metric for determining the magnitudes of on-fault and diffuse crustal deformation, which are proportional to fault slip rates and strain rates within crustal micro-plates, respectively. We simultaneously estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
144
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(175 citation statements)
references
References 85 publications
20
144
1
Order By: Relevance
“…More broadly, our results show that the northern Karakoram fault does not currently form a discrete kinematic boundary within the Himalayan-Tibetan orogen between the Pamir-Karakoram region to the west and the Tibetan Plateau to the east, as assumed in many kinematic and geodynamic models (Avouac and Tapponnier, 1993;He and Chéry, 2008;Liu and Bird, 2008;Loveless and Meade, 2011;Meade, 2007;Peltzer and Saucier, 1996). Instead, the dynamics of the two regions may be partially coupled, or more likely decoupled over a broad region of diffuse deformation, a feature that future kinematic and mechanical models of recent to active deformation in the Tibetan orogen will need to take into consideration.…”
Section: Broader Tectonic Implicationsmentioning
confidence: 85%
See 2 more Smart Citations
“…More broadly, our results show that the northern Karakoram fault does not currently form a discrete kinematic boundary within the Himalayan-Tibetan orogen between the Pamir-Karakoram region to the west and the Tibetan Plateau to the east, as assumed in many kinematic and geodynamic models (Avouac and Tapponnier, 1993;He and Chéry, 2008;Liu and Bird, 2008;Loveless and Meade, 2011;Meade, 2007;Peltzer and Saucier, 1996). Instead, the dynamics of the two regions may be partially coupled, or more likely decoupled over a broad region of diffuse deformation, a feature that future kinematic and mechanical models of recent to active deformation in the Tibetan orogen will need to take into consideration.…”
Section: Broader Tectonic Implicationsmentioning
confidence: 85%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) He and Chéry, 2008;Liu and Bird, 2008;Loveless and Meade, 2011;Meade, 2007;Peltzer and Saucier, 1996;Thatcher, 2007;Valli et al, 2007) (Fig. 1A and B).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recent studies have suggested that this slip-rate gradient may be accommodated by internal deformation within the plateau and regional clockwise rotation of the Kunlun fault Kirby and Harkins, 2013), and/or that displacement is transferred northward, across the interior of northeastern Tibet, to the Haiyuan fault . A recent inversion of geodetic and geologic data suggests that slip along the Elashan and Riyueshan faults could indeed accommodate slip-rate gradients along the eastern Kunlun fault (Loveless and Meade, 2011), but this model requires relatively high rates of slip (~4-6 mm/yr) along these structures in order to accomplish complete transfer of slip. Geologic and geomorphic data suggest that right-lateral slip rates along the Elashan and Riyueshan faults are only ~1 mm/yr , such that signifi cant deformation must occur between the Kunlun and the Haiyuan faults on other structures in addition to the Elashan and Riyueshan faults .…”
Section: Introductionmentioning
confidence: 98%
“…These faults were relatively quiescent in seismicity (Loveless and Meade 2011;Meade 2007). Source inversions based on teleseismic data showed a pattern of double-peak energy release during rupture (e.g., Ji and Hayes 2008;Nakamura et al 2010;Zhang and Ge 2010;Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 99%